2018
DOI: 10.1101/262576
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neural Signatures of Reward and Sensory Prediction Error in Motor Learning

Abstract: 22Two distinct processes contribute to changes in motor commands during reach adaptation: 23 reward based learning and sensory error based learning. In sensory error based learning, the 24 mapping between sensory targets and motor commands is recalibrated according to error 25 feedback. In reward based learning, motor commands are associated with subjective value, 26 such that successful actions are reinforced. We recorded EEG from humans of either sex to 27 identify and dissociate the neural correlates of rew… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 82 publications
2
11
0
Order By: Relevance
“…However, the fMRI investigation did show increased ACC activity in response to execution versus selection errors, suggesting that execution errors have their own neural signature. Relatedly, the FRN has been shown to vary in response to reward prediction errors but not sensory prediction errors when comparing signals from reward and visuomotor rotation learning tasks (Palidis et al, 2019). Together with the fMRI results, the present data pose the possibility that execution error processing may be distinct from dopamine-related reinforcement learning processes.…”
Section: Differential Error Processing Indexed By the Mfnsupporting
confidence: 58%
“…However, the fMRI investigation did show increased ACC activity in response to execution versus selection errors, suggesting that execution errors have their own neural signature. Relatedly, the FRN has been shown to vary in response to reward prediction errors but not sensory prediction errors when comparing signals from reward and visuomotor rotation learning tasks (Palidis et al, 2019). Together with the fMRI results, the present data pose the possibility that execution error processing may be distinct from dopamine-related reinforcement learning processes.…”
Section: Differential Error Processing Indexed By the Mfnsupporting
confidence: 58%
“…With respect to the ERP analyses, we expected to confirm that the FRN encodes PE in an active learning condition (Fischer & Ullsperger, ; Holroyd & Coles, ; Palidis et al, ; Walsh & Anderson, ). Therefore, we predicted a relationship between neural activity in the FRN time window and the trialā€byā€trial magnitude of modelā€generated PEs.…”
Section: Introductionmentioning
confidence: 94%
“…This aspect of human behavior is formalized in Reinforcement Learning (RL) Theory, which states that the subjective value of an action is updated when there is a discrepancy between the predicted and actual outcome of an actionā€”a prediction error (PE) (Barto & Sutton, ). PE computations are represented physiologically in electroencephalogram (EEG) signal in the form of the feedbackā€related negativity (FRN), also referred to as the reward positivity (RewP) (Proudfit, ), which is an eventā€ related potential (ERP) that correlates positively with PE (Fischer & Ullsperger, ; Gehring & Willoughby, ; Holroyd & Coles, ; Palidis, Cashaback, & Gribble, ; Walsh & Anderson, ) and whose likely origin is the posterior medial frontal cortex (pMFC) (Gehring & Willoughby, ; Gruendler, Ullsperger, & Huster, ; Holroyd & Coles, ; Palidis et al, ; Walsh & Anderson, ).…”
Section: Introductionmentioning
confidence: 99%
“…Perturbations also elicit either an unexpected failure to attain the reward of hitting the target (i.e., a negative reward prediction error) (Izawa & Shadmehr, 2011), and/or an unexpected punishment of missing the target (i.e., a positive punishment error). It is clear that behavioural responses to perturbations are affected not only by sensory prediction errors, but also by reward prediction errors (Izawa & Shadmehr, 2011; Cashaback et al , 2017; Palidis et al , 2018). However, how reward prediction errors and rewards affect sensorimotor adaptation is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, sensory prediction errors are known to result in implicit remapping: a change in the perceived sensory consequences of motor command (Mazzoni & Krakauer, 2006). Although adaptive behaviour to compensate for perturbations can be driven by sensory prediction errors or reward prediction errors (Izawa & Shadmehr, 2011; Nikooyan & Ahmed, 2015; Cashaback et al , 2017; Palidis et al , 2018), it has been suggested that only sensory prediction errors can produce a change in the system that predicts sensory consequences of motor commands: reward prediction errors alone are insufficient (Izawa & Shadmehr, 2011; Nikooyan & Ahmed, 2015). However, because these studies never made both sensory prediction errors and reward prediction errors concurrently available in the same conditions, it remains unclear whether reward prediction errors modulate implicit remapping resulting from sensory prediction errors.…”
Section: Introductionmentioning
confidence: 99%